1981
DOI: 10.1152/ajpheart.1981.241.4.h564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental volume-overload hypertrophy on myocardial blood flow and cardiac function

Abstract: To examine the effects of volume-overload hypertrophy on regional myocardial perfusion, we determined myocardial blood flows with microspheres at rest, during exercise, and during exercise with adenosine infusion in dogs with aortocaval fistulas for 12 wk (group 2) and sham-operated controls (group 1). A subgroup of six animals (group 3) was studied both before and after shunt closure in order to separate the influences of hypertrophy from the hemodynamic effects of the fistula. Epicardial blood flows in anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Adaptation also occurs in large arteries as Villari et al [191] found increased cross-section of the left anterior descending coronary artery in patients with aor tic valve deficiency, which regressed after valve replace ment. As a result of these changes there is no impairment of minimal coronary resistance [192,193] or maximal perfusion [166,185,194], Fewer attempts have been made to improve vascular supply in volume overload than in pressure overload hy pertrophy. Pacing-induced bradycardia started 1 month after aortic valve lesion in rabbits, increased capillary density by 60% within 4 weeks in comparison with unpaced hypertrophic hearts, and by 20% compared to control hearts, although it only marginally diminished the degree of hypertrophy [195], It also normalised coronary reserve ratio which was decreased bv hvpertrophv ( fig.…”
Section: Vesselsmentioning
confidence: 99%
“…Adaptation also occurs in large arteries as Villari et al [191] found increased cross-section of the left anterior descending coronary artery in patients with aor tic valve deficiency, which regressed after valve replace ment. As a result of these changes there is no impairment of minimal coronary resistance [192,193] or maximal perfusion [166,185,194], Fewer attempts have been made to improve vascular supply in volume overload than in pressure overload hy pertrophy. Pacing-induced bradycardia started 1 month after aortic valve lesion in rabbits, increased capillary density by 60% within 4 weeks in comparison with unpaced hypertrophic hearts, and by 20% compared to control hearts, although it only marginally diminished the degree of hypertrophy [195], It also normalised coronary reserve ratio which was decreased bv hvpertrophv ( fig.…”
Section: Vesselsmentioning
confidence: 99%
“…Although the structural and biochemical alterations in hypertrophied muscle induced by chronic volume overload may cause ventricular dysfunction, there is no consensus in the literature on the mechanisms of heart failure. Experimental studies have shown either preserved [12–15] or depressed myocardial contractility [16,17] caused by aortocaval fistula in rats. Brower et al [17] showed that systolic ventricular dysfunction was related to chamber dilatation and increased compliance.…”
Section: Introductionmentioning
confidence: 99%
“…However, even when using these highly controlled conditions, researchers have reported conflicting results. In fact, myocardial hypertrophy has been described as a condition associated with decreased, unchanged, or even increased contractility when heart failure is absent (2,3,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). The possible causes for these discrepancies are many and may include the type of hypertrophy, the animal used in the study, the time course of the overload-induced hypertrophy, and the indexes used to measure contractility.…”
Section: Introductionmentioning
confidence: 99%